Dependency of Transport Functions on IEEE802.11 and IEEE802.15.4 MAC/PHY Layer Protocols for WSN: A Step towards Cross-Layer Design - Sharif, Atif; Potdar, Vidyasagar; Rathnayaka, Dinusha (IGI Global, 2010)
In WSN, transport layer protocol plays a significant role in maintaining the node’s energy budget. To find out the dependency of Transport layer on MAC/PHY layer, the authors have extensively tested various transport protocols using IEEE 802.11, IEEE 802.15.4 MAC/PHY protocols for WSN. For IEEE802.11 and IEEE802.15.4 with RTS/CTS ON the TCP variants has shown >80% packet delivery ratio and 5-20% packet loss, while for UDP it is around >63% and 19.54-35.18% respectively. On average 1-3% additional energy is consumed for packet retransmissions in IEEE 802.11 with RTS/CTS OFF whereas significant energy efficiency is observed in IEEE802.15.4 case. For IEEE 802.11 with RTS/CTS ON high throughput, low packet drop rate and increased E-2-E delay is observed, while for IEEE 802.15.4 improved power efficiency and jitter behavior is observed. This has led the foundation for the future development of the cross-layered energy efficient transport protocol for WSN.